Marpesia marcella (Felder)(Lepidopetra: Nymphalidae), nuevo reporte para la fauna de Nicaragua - Puig, J.=700 1 Cabrera, G.
(Es, En)
Ilus., 1 ref.
Keywords: LEPIDOPTERA; NYMPHALIDAE; DISTRIBUCION GEOGRAFICA; ESPECIES NUEVAS; FAUNA; NICARAGUA; MARPESIA MARCELLA; MARIPOSA; REVISTA NICARAGUENSE DE ENTOMOLOGIA